2003
DOI: 10.1038/sj.jhh.1001534
|View full text |Cite
|
Sign up to set email alerts
|

Renin-angiotensin-aldosterone system and G-protein beta-3 subunit gene polymorphisms in salt-sensitive essential hypertension

Abstract: Approximately 50% of hypertensive patients are salt sensitive (they increase their Blood Pressure in response to sodium intake or volume expansion). Mechanisms underlying salt sensitivity are not completely elucidated although there is evidence that they may be genetically determined. The aim of this study is to establish the relation among some genetic polymorphisms of the renin-angiotensin system (RAAS) and the beta-3 subunit of the protein G and salt sensitivity. We studied 102 essential hypertensive patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 32 publications
5
31
0
Order By: Relevance
“…The role of polymorphisms of both AGT M235T (Beeks et al 2004;Schorr et al 1999;Hunt et al 1999) and ACE I/D (Beeks et al 2004;Pamies-Andreu et al 2003;Dengel et al 2001) in salt-sensitive hypertension is controversial, although well-established evidence exists as to their role in hypertension, diabetic and nondiabetic nephropathy, and cardiovascular diseases (Cambien et al 1992;Schunkert et al 1994). In the present study, a statistically significant association was found for the TT genotype in hypertensive patients, as expected.…”
Section: Discussionsupporting
confidence: 75%
“…The role of polymorphisms of both AGT M235T (Beeks et al 2004;Schorr et al 1999;Hunt et al 1999) and ACE I/D (Beeks et al 2004;Pamies-Andreu et al 2003;Dengel et al 2001) in salt-sensitive hypertension is controversial, although well-established evidence exists as to their role in hypertension, diabetic and nondiabetic nephropathy, and cardiovascular diseases (Cambien et al 1992;Schunkert et al 1994). In the present study, a statistically significant association was found for the TT genotype in hypertensive patients, as expected.…”
Section: Discussionsupporting
confidence: 75%
“…Studies exploring its possible association with salt sensitivity and susceptibility to hypertension gave contrasting results [34][35][36]. In a recent study, Martin et al [37] found no association between this polymorphism and SSBP or prevalence of hypertension; nevertheless, they observed that plasma sodium concentration was higher and plasma potassium was lower in TT than in CC patients, a finding suggesting that increased NHE-1 activity is associated with the less common allelic variant of the gene.…”
Section: Recent Advances In the Genetics Of Salt-sensitive Hypertensionmentioning
confidence: 92%
“…There were 39 studies carried out in Asian populations, [19][20][21][22]57,58,61,63,65 while 15 studies were performed in Caucasian populations. [11][12][13]18,23,[54][55][56]59,60,62,64,[66][67][68] Only two studies involved an African population. 17,18 …”
Section: Baseline Characteristicsmentioning
confidence: 99%